PERANAN SIDIK JARI DALAM MENGUNGKAP PELAKU TINDAK PIDANA DI TINGKAT PENYELIDIKAN POLDA BALI - Arthadana, Made Gede (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 4 (2015), 2015)
The scientific paper entitled fingerprint role in uncovering criminal investigation at Polda Bali. The method used is the method of empirical research with normative and empirical approaches, legal materials used are the primary legal materials do research at Polda Bali and secondary legal materials using literature and official documents. The investigation by the police is to obtain the truth based on actual facts. One of the investigation conducted by the police using fingerprint identification. Fingerprints have two properties namely latent fingerprint and a real fingerprint. Methods fingerprints obtained by gathering evidence at crime scenes. But the weakness of the fingerprint that is easily damaged and quickly disappear, therefore the police must stand guard the crime scene in order to collect fingerprint evidence.
Keywords: Investigation; Police; Fingerprint